Double-standards in reporting of risk and responsibility for sexual health: a qualitative content analysis of negatively toned UK newsprint articles - Martin, Susan P (BioMed Central, 2014)
BACKGROUND: The need to challenge messages that reinforce harmful negative discourses around sexual risk and responsibility is a priority in improving sexual health. The mass media are an important source of information regularly alerting, updating and influencing public opinions and the way in which sexual health issues are framed may play a crucial role in shaping expectations of who is responsible for sexual health risks and healthy sexual practices. METHODS: We conducted an in-depth, qualitative analysis of 85 negatively toned newspaper articles reporting on sexual health topics to examine how risk and responsibility have been framed within these in relation to gender. Articles published in 2010 in seven UK and three Scottish national newspapers were included. A latent content analysis approach was taken, focusing on interpreting the underlying meaning of text. RESULTS: A key theme in the articles was men being framed as a risk to women’s sexual health, whilst it was part of a women’s role to “resist” men’s advances. Such discourses tended to portray a power imbalance in sexual relationships between women and men. A number of articles argued that it was women who needed to take more responsibility for sexual health. Articles repeatedly suggested that women and teenage girls in particular, lacked the skills and confidence to negotiate safer sex and sex education programmes were often presented as having failed. Men were frequently portrayed as being more promiscuous and engaging in more risky sexual health behaviours than women, yet just one article drew attention to the lack of focus on male responsibility for sexual health. Gay men were used as a bench mark against which rates were measured and framed as being a risk and at risk. CONCLUSIONS: The framing of men as a risk to women, whilst women are presented at the same time as responsible for patrolling sexual encounters, organising contraception and preventing sexual ill health reinforces gender stereotypes and undermines efforts to promote a collective responsibility for sexual health. This has implications for sexual ill health prevention and could continue to reinforce a negative culture around sex, relationships and sexual health in the UK.